생육 지표와 기상 정보를 이용한 중만생종 양파 구중 예측 - 김지수; 김선웅 (농촌경제, 2021)
This study develops a forecasting model for bulb weight of median-late variety onion to alleviate supply-demand imbalance. The actual measurement data in 2020/2021 are from the Korea Rural Economic Institute (KREI). A multilevel model is applied to reflect the hierarchical data characteristics consisting of growth indicators in individual units and meteorological factors in parcel units. The results are as the following: The harvest timing should be considered when constructing the forecasting model since the weights vary depending on that. The growth indicators, especially the number of leaves, at the early bulb enlargement period and the number of optimum temperature days during the bulb enlargement period show the positive effects on the bulb weight at the harvest. It is possible to forecast the growth indicators at the early bulb enlargement period using those at the early leaf elongation period. When applying the estimation results for 2020 and 2021 data, the growth indicators at the early bulb enlargement period can be explained as much as about 90% based on those at the early leaf elongation period.